1200. Parent Perspectives on Infection Prevention and Control in the NICU - Science, Michelle (Open Forum Infect Dis, 2019)
BACKGROUND: Infants admitted to the neonatal intensive care unit (NICU) are at high risk for healthcare-associated infections (HAIs) due to their immature immune systems and need for invasive devices. Parents have frequent contact with their infants and present an opportunity for prevention practices. The objective of this study was to evaluate parental opinions related to infection prevention and control (IPAC) in the NICU. METHODS: An online survey was sent to a network of 2,000 parents from the Canadian Premature Babies Foundation. The survey included questions about patient-centered outcomes, IPAC practices experienced during their infants’ NICU admission, and specifically, opinions regarding nonsterile glove use by both healthcare workers (HCWs) and parents. RESULTS: A total of 72 parents responded to the survey. The majority were parents of infants born at less than 37 weeks (94%) and had been admitted to an NICU after 2010 (89%). When asked about preventing infections in the NICU, 82% of parents indicated they had been given information on how the NICU prevents infection and 96% had been told how they can prevent infection in their infant (Table 1). The most common information was related to hand hygiene (96%) and what to do if they were unwell (89%). Opportunities for improvement included being bare below the elbow, nail care, and feeding human milk. With respect to IPAC outcomes of interest, 96% agreed that it was important to study interventions to reduce bloodstream infections (BSIs). Other outcomes of interest (Table 2) included necrotizing enterocolitis (72%), antibiotic-resistant organism acquisition (69%), and length of stay (67%). With respect to glove use, 89% of parents felt that it was acceptable for HCWs to wear gloves when caring for their infant. Only 37% of parents indicated that they would want to wear gloves if HCWs were wearing gloves, but 47% would consider wearing gloves if there was evidence that it reduced infection in their infant. CONCLUSION: Reducing infections, specifically BSIs, in infants admitted to the NICU is an outcome of interest for parents. Nonsterile gloving by HCWs is considered an acceptable strategy by parents to reduce infections. Missed opportunities exist for the education of parents in the NICU on IPAC practices. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.